Why do I treat HBeAg‐negative chronic hepatitis B patients with pegylated interferon?. (3rd January 2013) - Lampertico, Pietro; Viganò, Mauro; Colombo, Massimo
Abstract: Chronic hepatitis B (CHB) in serum HBeAg negative patients is a difficult to cure, progressive disease leading to end‐stage liver disease and hepatocellular carcinoma. Currently, there are two different treatment strategies for such patients: a finite course of Pegylated interferon (PEG‐IFN) or long‐term administration of the more potent and less resistance‐prone nucleot(s)ide analogues (NUC), i.e. entecavir and tenofovir. Although NUC may ensure persistent viral suppression by preventing disease progression in most patients, they require lifelong administration with the hypothetical disadvantages of cost, lack of long‐term safety data and, most important, the null rates of HBsAg seroclearance. On the other hand, 1 year of PEG‐IFN has the advantage of providing an immune‐mediated control of hepatitis B virus (HBV) infection, with the possibility of achieving a sustained off‐treatment response in 20% of the patients, ultimately leading to HBsAg loss in approximately 50% of these. However, these sustained response rates can be significantly increased by carefully selecting candidates for PEG‐IFN therapy based upon baseline ALT and HBV DNA levels, viral genotype and IL28B polymorphisms, by extending PEG‐IFN therapy beyond 48 weeks and, most importantly, by applying early on‐treatment stopping rules based upon HBsAg kinetics. Overall, PEG‐IFN is an ideal treatment strategy in selected patients with HBeAg‐negative CHB, because of its well‐recognized and predictable safety profile and a unique mechanism of antiviral activity leading to long‐lasting immune control. Because of these features, new therapeutic trials based upon a combination of PEG‐IFN and third generation NUC such as entecavir and tenofovir, in both naïve and NUC‐exposed patients, are ongoing to further increase the rates of HBsAg seroclearance, which remains the 'ideal end‐point' in all HBeAg‐negative CHB subjects.